Prolonged Cycle Times and Schedule Growth in Defense Acquisition A Literature Review - Riposo, Jessie (RAND Corporation, 2014)
This report summarizes a selection of the defense acquisition literature from the 1960s to the present on potential sources of prolonged acquisition cycle times and schedule growth, as well as potential opportunities for improvement. It presents the range of possible causes of schedule-related problems and various recommendations cited for improving schedules by various authors and organizations.